Innate and humoral recognition of the products of cell death: differential antigenicity and immunogenicity in lupus. (5th December 2016) - Arora, P.; Malik, M.; Sachdeva, R.; Saxena, L.; Das, J.; Ramachandran, V. G.; Pal, R.
Summary: While apoptotic debris is believed to constitute the original antigenic insult in lupus (which is characterized by a time‐dependent diversification of autoreactivity), whether such debris and autoantibodies specifically recognizing its constituents mediate differential effects on innate and humoral responses in lupus‐prone mice is currently unknown. Apoptotic blebs (as opposed to cellular lysate) enhanced preferentially the maturation of dendritic cells (DCs) from bone marrow precursors drawn from lupus‐prone mice. Murine, somatically mutated, apoptotic cell‐reactive immunoglobulin (Ig)G monoclonal antibodies demonstrated enhanced recognition of DCs and also displayed a prominent lupus strain‐specific bias in mediating DC maturation. Further, immunization of such antibodies specifically in lupus‐prone mice resulted in widespread humoral autoreactivity; hypergammaglobulinaemia (a hallmark of systemic autoimmunity) was observed, accompanied by enhanced antibody titres to cellular moieties. Induced antibodies recognized antigens distinct from those recognized by the antibodies employed for immunization; in particular, nephritis‐associated anti‐double stranded (ds) DNA antibodies and neonatal lupus‐associated anti‐Ro60 antibodies were elicited by a non‐dsDNA, non‐Ro60 reactive antibody, and Sm was a favoured target. Further, only in lupus‐prone mice did such immunization enhance the kinetics of humoral anti‐self responses, resulting in the advanced onset of glomerulosclerosis. These studies reveal that preferential innate and humoral recognition of the products of cell death in a lupus milieu influence the indices associated with autoimmune pathology. Abstract : Apoptotic blebs and apoptotic cell‐reactive antibodies are deferentially‐recognized by the innate and adaptive immune systems in lupus. Downstream events arising as a consequence of such recognition may serve to precipitate pathology.